"Through the looking glass: envisioning new library technologies" telling stories with technology. Issue 9 (2nd November 2015) - Fernandez, Peter
Abstract : Purpose: – This column aims to explore the technologies that are enabling libraries, and the communities they serve, to easily tell their own stories. Design/methodology/approach: – Point of view. Findings: – Libraries can facilitate the acquisition of technology and literacies necessary to make recording, sharing and preserving stories of all kinds easy for library patrons. Practical implications: – Libraries collect, preserve and help distribute information to serve their communities. Originality/value: – By facilitating access to these emerging mediums, libraries can both empower their communities and play an active role in preserving their communities' histories.